(untitled) (Raparin Journal of Humanities (RJH), 2020)
A deeply complicated situation characterizes Mesopotamia and its neighborhood, with a lasting solution to the fate of minorities in the region yet to be comprehended. In this secondary study, the central purpose is to investigate issues and the fate of Christians in the Nineveh Plains, ranging from their dream for self-governance to the displaced nightmare. Particularly, the study seeks to gain insight into prospects of self-governance for minorities, shedding light on some of the platforms that the affected communities could exploit to realize this dream, as well as major hurdles that they might encounter. The study’s specific objectives include the examination of the current degree of success in Iraqi minorities’ quest for self-governance, some of the challenges facing the community, and some of the feasible solutions that are worth embracing. From the findings, some of the challenges facing Iraqi minorities’ quest for self-governance are seen to include the KRG harassment and land seizures and the labelling of Yazidis as Kurds due to political factors, translating into irritation. Another hurdle is that Peshmerga soldiers are an unpredictable threat, especially after they abandoned Yazidi and Christian villages during the onslaught by ISIS. Therefore, self-governance and self-determination are the key factors that would necessitate chances of Iraqi minorities’ survival, but the reconciliation process requires interventions by international organizations such as those in the West, with the United States Institute of Peace (USIP) unexceptional.